2016
DOI: 10.3389/fpls.2016.01032
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide QTL Mapping for Wheat Processing Quality Parameters in a Gaocheng 8901/Zhoumai 16 Recombinant Inbred Line Population

Abstract: Dough rheological and starch pasting properties play an important role in determining processing quality in bread wheat (Triticum aestivum L.). In the present study, a recombinant inbred line (RIL) population derived from a Gaocheng 8901/Zhoumai 16 cross grown in three environments was used to identify quantitative trait loci (QTLs) for dough rheological and starch pasting properties evaluated by Mixograph, Rapid Visco-Analyzer (RVA), and Mixolab parameters using the wheat 90 and 660 K single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 83 publications
(114 reference statements)
3
64
0
Order By: Relevance
“…The genetic length of this map was 2875.3 cM, similar to reported maps in hexaploid wheat (Somers et al, 2004; Wu et al, 2015b). Notably, the high number (11,646) of polymorphic SNP markers between Y8679 and J411 is comparable to Jin et al (2016) and Perez-Lara et al (2016), who detected 12,205 and 10,342 polymorphic SNPs between two parental lines, respectively. Collectively, these data suggest that the iSelect 90K array is a powerful tool for genotyping analysis in hexaploid wheat.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The genetic length of this map was 2875.3 cM, similar to reported maps in hexaploid wheat (Somers et al, 2004; Wu et al, 2015b). Notably, the high number (11,646) of polymorphic SNP markers between Y8679 and J411 is comparable to Jin et al (2016) and Perez-Lara et al (2016), who detected 12,205 and 10,342 polymorphic SNPs between two parental lines, respectively. Collectively, these data suggest that the iSelect 90K array is a powerful tool for genotyping analysis in hexaploid wheat.…”
Section: Discussionsupporting
confidence: 77%
“…Collectively, these data indicated that both the iSelect 9K and 90K arrays have considerable limitations when dealing with the D genome. Therefore, studies focusing on chromosomes from the D genome are recommended to use much larger genotyping platforms, such as the recently developed 660K SNP chip (Jin et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…13b and c). We also found that a flour-quality QTL 52 overlaps with a selected region on chromosome 6B.…”
Section: Resultssupporting
confidence: 52%
“…Using F ST -θ π , XP-EHH, and XP-CLR analyses, we identified 22.75-Mb (covering 1,760 genes), 3.00-Mb (covering 1,074 genes), and 21.04-Mb (covering 2,619 genes) putatively selected regions between the European and West Asian landraces, respectively (Supplementary Table 10). These selected regions overlap with a few reported QTLs, including two associated with flour quality 52 . We identified a significantly selected region on chromosome 2B that contains TaNPF6.1-2B , another ortholog of the Arabidopsis nitrate transporter gene NRT1.1 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Performing these evaluations at a late stage in the breeding program often results in ostensibly promising wheat lines with high yield and resistance to diseases that cannot be released due to poor end-use quality traits, such as a weak performance for milling parameters and baking properties. To address these challenges, many studies have been conducted to identify quantitative trait loci (QTL) and associated markers for end-use quality traits, with the aim to use such markers in marker-assisted selection (MAS) to improve quality traits in early generations of the breeding program (Campbell et al 2001; Groos et al 2003; Prasad et al 2003; Breseghello et al 2005; Kulwal et al 2005; Arbelbide and Bernardo 2006; Breseghello and Sorrells 2006; Huang et al 2006; Kuchel et al 2006; Kunert et al 2007; Mann et al 2009; Tsilo et al 2010; Zhao et al 2010; Carter et al 2012; Li et al 2012a; Simons et al 2012; El-Feki et al 2013; Mergoum et al 2013; Deng et al 2015; Echeverry-Solarte et al 2015; Tiwari et al 2016; Jin et al 2016). It should be mentioned that MAS for end-use quality traits would be commenced from F 5 generation onwards if a single seed decent (SSD) method is used to develop wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%